The postharvest application of biodegradable polymers and a priming agent as a potential tool to enhance phytochemical content, aroma profile and market life of strawberry fruit - Georgiadou, Egli C.; Garcia Hernandez Gil, Carlos Javier; Taliadorou, Anna-Maria; Myrtsi, Eleni D.; Gohari, Gholamreza; Varaldo, Alice; Torrado, Sofia O.C.A.; Gasperini, Alessandra Marcon; Tomás-Barberán, Francisco A.; Hertog, Maarten L.A.T.M.; Fotopoulos, Vasileios; Manganaris, George A. (My University, 2025)
Strawberry (Fragaria x ananassa Duch.) is a highly perishable crop with limited market life. The aim of our work was to dissect the efficacy of an array of molecules with potential priming effect on postharvest performance, antioxidant potential and aroma profile of strawberry fruit. Freshly harvested fruit (cv. ‘Savana’) of uniform size and ripening stage (commercial ripeness >80 % of the surface red color) were subjected to the following postharvest dip treatments: control (untreated), hydro-primed, NOSH-A, chitosan (CTS) and sodium alginate (NaA). NOSH-A is a proprietary priming agent that acts as a donor that releases nitric oxide (NO), hydrogen sulfide (H2S), and aspirin (acetylsalicylic acid) concurrently. CTS is a biobased, biologically safe and biodegradable polymer that has been exploited as a nanocarrier to efficiently deliver an array of compounds, while NaA is another biodegradable polymer applied in smart nano-delivery systems. Treated fruit were subjected to 4, 8 and 12 d of cold storage (CS, 4 °C, 90 % RH) and additional maintenance at room temperature for 1 d to simulate short, medium and extended refrigerated storage, respectively. Quality attributes and fungal incidence and severity were determined, without any striking differences among the treatments applied. Polyphenolic compounds analysis by HPLC-DAD-ESI-MS/MS showed an increment in an array of phytochemical compounds such as ellagic acid, pelargonidin-3-glucoside, pelargonidin-3-rutinoside, and catechin, particularly after 8 days CS compared to fleshly harvested fruit. Such changes were more evident when the priming agent NOSH-A was applied, being more pronounced in the case of pedunculagin 2 isomer that registered a significant increment. HS-SPME-GC analysis identified 140 unique volatile organic compounds (VOCs) with chitosan-treated strawberries showing the most distinct VOC profile after extended cold storage with higher contents of methyl hexanoate. Results reported herein shed light in the efficacy of an array of agents on parameters linked to secondary metabolism of strawberry fruit at postharvest level.
Keywords: Fragaria x ananassa; Chitosan; Alginate; Phytochemicals; Phenolic acids; Cold storage